Literasi, Numerasi, dan Adaptasi Teknologi Bagi Guru Sekolah Dasar - Maria Ulfa; Dyah Anungrat Herzamzam ; Nur Syahana Permata Ningsih; Dessy Yulistianingsih; Hasya Asriani Ritonga (Pusat Riset dan Inovasi Nasional, 2024)
The development of ICT has an impact on the education sector. In Indonesia itself, the development of ICT is not balanced with literacy and numeracy skills. There needs to be follow-up on the low literacy and numeracy skills of students. Follow-up should not only focus on student abilities, but should also be teacher-centered. PGSD Study Program, STKIP Kusuma Negara, through the Field Work Lecture (KKL) course, implements the tri dharma of higher education, namely Community Service (PKM) in the form of a national webinar with the theme My Teacher, My Hero - Literacy and Numeracy in the Digital Era for Elementary School Teachers. PKM implementation goes through 3 stages, namely pre-preparation, implementation and post-implementation stages. The training was conducted with 2 resource persons and attended by 268 participants who were elementary school teachers and students from all over Indonesia.